Contacts and Opposition between Russian and European Art in the 16th Century: Some Observations - Smirnova, Engelina S. (Actual Problems of Theory and History of Art, 2016)
The peculiar interpretation of West-European motifs in Russian culture can be traced centuries back, mainly in architecture, decoration of church façades, decorative arts, and ornamentation of manuscripts. The reflection of West-European motifs in Russian painting of the 16th century can be seen in the drawings of “Gothic” buildings on the background of compositions, and, sometimes, in the stylistic elements (contours of the figures and representation of postures and movements).The other side of the Russian-European contacts in the 16th century is associated with the struggle of Moscow Rus’ against the negation of truth of sacred images, i.e. against the idea which was one of the characteristic features of Protestantism. The pictures of Christ on the Mandylion or on the Keramion in Russian art are accompanied by the inscriptions “Image of Savior”, sometimes with addition “Not Made by Hand”. There are scenes in the Virgin’s iconography representing the evangelist Luke painting her image (sometimes in presence of the Mother of God herself) with the aid of an angel symbolizing the Divine Wisdom. As for the saints, the truth and variety of their miracles are underlined by their images. These ideas are most intensively realized in the iconography of Saint Nicholas of Myra. Russian icon painters represent Christ and the Virgin giving Saint Nicholas the book of Gospels and omophorion (the attributes of his bishop’s dignity), while the angels are helping him to realize his acts.